Efficacy of chemical sphincterotomy with 2% diltiazem cream vs. surgical sphincterotomy in the management of chronic fissure in ano: a clinical study - Kenche, Jeevan; Reddy, Chandrashekhar (International Surgery Journal, 2018)
Background: Surgical intervention like lateral internal sphincterotomy is very effective and in a time of few weeks, healing can occur but there is danger of the anal incontinence. Hence alternative methods were sought like 2% diltiazem and other agents and they have been shown to lead to proper healing without anal incontinence. The objective was to study efficacy of chemical sphincterotomy with 2% diltiazem cream vs. surgical sphincterotomy in the management of chronic fissure in ano. Methods: A hospital based follow up study was carried out among 60 patients with chronic fissure in ano. They were randomly assigned in two groups. Group I consisted 30 patients who were treated with 2% diltiazem cream on outpatient basis. Group II patients i.e. 30 patients were operated for sphincterotomy. Both the group patients were followed for six weeks at two weeks interval. Outcome like complete healing, fecal incontinence, flatus incontinence was seen at follow up. Chi square test and t test were used to determine the significant difference between the groups. Results: Both the groups were comparable to each other in terms of age, sex, presenting symptoms, mean duration of symptoms and internal findings. Diltiazem group patients had significantly much better healing rate i.e. 96.7% compared to only 80% from patients with surgery group. Incidence of complications like fecal/flatus incontinence was zero in diltiazem group compared to 13.3%/20% in surgery group. Conclusions: Authors conclude that diltiazem 2% topical application is better than surgical sphincterotomy and should be used instead of surgery.